CB2 and GPR55 Receptors as Therapeutic Targets for Systemic Immune Dysregulation - Zhou, Juan; Burkovskiy, Ian; Yang, Hyewon; Sardinha, Joel; Lehmann, Christian (Frontiers in Pharmacology, 2016)
The endocannabinoid system (ECS) is involved in many physiological processes and has been suggested to play critical roles in the immune response and the central nervous system (CNS). Therefore, ECS modulation has potential therapeutic effects on immune dysfunctional disorders, such as sepsis and CNS injury-induced immunodeficiency syndrome (CIDS). In sepsis, excessive release of pro- and anti-inflammatory mediators results in multi-organ dysfunction/failure and death. In CIDS, an acute CNS injury dysregulates a normally well-balanced interplay between the CNS and immune system, leading to increased patients’ susceptibility to infections. In this review, we will discuss potential therapeutic modulation of the immune response in sepsis and CNS injury by manipulation of the ECS representing a novel target for immunotherapy.